Co-CeOx nanoparticles anchored on a nitrogen-doped carbon nanosheet: a synergistic effect for highly efficient hydrolysis of sodium borohydride. Issue 4 (22nd December 2020) - Yao, Longhua; Li, Xiugang; Peng, Wenfang; Yao, Qilu; Xia, Jianhui; Lu, Zhang-Hui
Abstract : Amorphous and electron-rich Co-CeO x nanoparticles anchored on a N-doped porous carbon nanosheet show remarkable catalytic performance for the hydrolysis of sodium borohydride. Abstract : Hydrolytic dehydrogenation of sodium borohydride (NaBH4 ) has been considered as a source of hydrogen for fuel cell applications. In this work, amorphous and electron-rich Co-CeO x nanoparticles (NPs) with a small size of 4.4 nm anchored on a nitrogen-doped carbon nanosheet (NCNS) have been prepared via a simple and facile chemical reduction method, in which NCNS was obtained by carbonizing a mixture of metal–organic frameworks ZIF-8 and potassium citrate. The as-prepared Co-CeO x /NCNS catalyst possesses an outstanding catalytic activity for the catalytic hydrolysis of NaBH4 at room temperature under alkaline conditions, giving a hydrogen generation rate (HGR) value as high as 28 410 mLH2 ·min −1 ·gCo −1, which is among the highest HGR values reported to date for all catalysts. The kinetics of hydrolytic dehydrogenation of NaBH4 aqueous solution was investigated in detail. The excellent catalytic activity of Co-CeO x /NCNS can be owing to the small size and amorphous state of Co-CeO x NPs, electron-rich properties of Co NPs modulated by the CeO x promoter, strong synergistic interaction between Co-CeO x NPs and the NCNS support with a high surface area and abundant defects, and the promotion of NaOH.